The Role of E-Commerce for MSMEs: A Study on Artificial Intelligence Training at Shopee Training Center - Hendrarso, Panji; Poernomo, Baby Sri Murniyati; Pather, Sulochini (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The Indonesian government ensures that MSMEs will once again become heroes of national economic revival in 2023. Currently there are around 20 million MSMEs that have been digitalized or on board on e-commerce platforms from the target of 30 million by early 2024. However, until now, there are still many MSMEs who think that Artificial Intelligence (AI) technology is only intended for large-scale businesses, so they are afraid or reluctant to take part in the training provided. This research is a qualitative study with a case study approach. Data collection was carried out through in-depth interviews with MSMEs from Central Java, East Java, South Sulawesi, East Kalimantan and Bali. The aim is to obtain data and information regarding how to implement Artificial Intelligence training and mentoring programs for MSMEs, what obstacles are encountered in implementing the training, and what solutions can be taken to overcome these obstacles. The results of this research show that training related to AI or digital technology organized by the Shopee Training Center can be well received by MSME players because the material is relevant to their needs, the instructors are competent and professional, the facilities provided are very complete with assistance for the participants who have completed the training.